Effect of paracetamol treatment on maternal care and reproductive outcomes in female rat offspring - Aleixo, Jeberson F.; Pereira, Marina R. F.; Montagnini, Bruno G.; Pereira, Matheus Junior D.; Forcato, Simone; Moreira, Estefania G.; Ceravolo, Graziela S.; Vieira, Milene L.; Kiss, Ana C. [UNESP]; Gerardin, Daniela C. C. (Csiro Publishing, 2020)
Paracetamol (PAR) is one of the most commonly used drugs by pregnant women because it is considered safe for the mother and fetus. However, PAR is transferred into breast milk and crosses the blood-placental barrier, being present in the progeny during important stages of development. Intrauterine exposure to PAR may decrease the anogenital distance and follicle reserve in female rodent offspring. Therefore, the aim of the present study was to evaluate whether maternal PAR treatment altered the reproductive behaviour of dams and the sexual development of female rat offspring. Pregnant Wistar rats were gavaged daily with 350 mg kg(-1) day(-1) PAR or water during gestation (from Gestation Day (GD) 6 until delivery) or during gestation and lactation (from GD6 until weaning). Maternal PAR treatment had maternal effects (increased grooming behaviour), and resulted in impaired sexual behaviour, decreased follicle reserve and increased plasma oestradiol concentrations in female offspring.
Keywords: acetaminophen; histology; maternal behaviour; ovaries; sexual behaviour